Regioselective synthesis of some functionalized 3,4’-bis-(pyrazolyl)ketones and chemoselectivity in their reaction with hydrazine hydrate - Hassaneen, Hamdi Mahmoud; Shawali, Ahmad Sami (European Journal of Chemistry, 2013)
A new enamino ester, (E)-ethyl 3-(dipropylamino)acrylate, was prepared and used for synthesis of various pyrazole derivatives, 4a-k and 5a-d. Other new enaminone, (E)-ethyl 3-(3-(dimethylamino)acryloyl)-1-(4-nitrophenyl)-1H-pyrazole-4-carboxylate (8), was also prepared from compound 4a and utilized as precursor for synthesis of different functionalized 3,4’-bis-pyrazolyl ketones 9a-c, 10a-c. The site selectivity in hydrazinolysis of the latter was studied. The structures of the products namely pyrazolo[3,4-d]pyridazine derivatives 11(13) were confirmed by spectral and elemental analyses and by alternate unambiguous synthesis.